Budaya Aimai dalam Anime Flying Witch Karya Katsushi Sakurabi - Devi Haryanti Oktavia; Mangatur Sinaga; Intan Suri (Ayumi : Jurnal Budaya, Bahasa, dan Sastra, 2022)
In Japanese society, one of the communication cultures that becomes an important concern is the aimai or ambiguity. The use aimai in community communication aims to maintain harmony. Aimai as a communication culture is not only used in real situations in society, but is also expressed in works such as anime, films, and manga. One of which is an anime entitled Flying Witch. The purpose of this research is to find out how the form and use of aimai in the anime Flying Witch. The findings of this study are useful as a theory development about culture that influences Japanese communication. With knowledge of culture in a language community, communication will work well. This research is a qualitative descriptive study. The theory used in this study is the theory of Davies and Ikeno (2002) and the theory of Tsuji Daisuke (1999). The results of the study stated that aimai in Japanese can be in the form of words, sentences, and interrogative sentences. Aimai in the Flying Witch anime is used to express opinions indirectly, disguise disapproval, and express doubt or uncertainty. Keywords: aimai; communication; culture.